Preserving Tay Kak Sie Temple: Negotiating Religious Function, Cultural Tourism, and Heritage Governance in Semarang - Hani, Adinda Ummu; Karimah, Nisrina Azmi; Nuraini, Laili Ulfa; Ramadhan, Fauzan Syahru; Amalia, Anindita Fikri (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
This study examines the resilience of Semarang’s oldest Chinese temple, Tay Kak Sie (est. 1746), in the face of contemporary preservation challenges. Using a cultural history methodology, by employing the critical historical method with data gathered through field observations, interviews, and historical documentation, this study analyzes the historical and cultural importance of Tay Kak Sie Temple, looking at its role as both a place for Tri Dharma worship and a religious tourism site. However, its preservation is constrained by limited funds, especially for the restoration of the original wooden structure of the temple's main room dating back to 1771. The findings reveal a significant gap between policy and practice; although the state is designated as a primary stakeholder under Government Regulation No. 1 of 2022, local government involvement in the management of Tay Kak Sie Temple remains minimal. Consequently, the burden of preservation is shifted to private foundations and community donations, a model that is increasingly strained by economic fluctuations and limited commercial growth within the Chinatown district. Furthermore, cultural engagement is found to be ethnically concentrated, as the lack of broader public participation prevents the site from becoming a space for active intercultural dialogue. To ensure long-term sustainability, a collaborative synergy involving government, academic, and community stakeholders is necessitated. This research underscores the critical need for integrated management strategies to prevent the structural decay and cultural marginalization of urban heritage sites in Indonesia.